비내진 상세를 가진 조적채움벽의 내진성능평가 - 박병태; Byung Tae Park; 권기혁; Ki Hyuk Kwon (한국안전학회지, 2017)
Masonry walls which are commonly used for partitions in low-rise reinforced concrete (RC) structures, can be easily exposed to high risks under strong earthquakes. Since the strength degradations cannot be protected under the ground motions, their applications cannot be recommended for building structures which are designed to possess high seismic performances. However, masonry-infilled walls are typically considered as non-structural elements in evaluating the seismic performance of building structures. In order to figure out this problem, this study performed experiments using two specimens-only RC frame and RC frame infilled with masonry walls- under static loading. Also, the study established analytical models representing fully infilled frames and bare frame, and compared their structural behavior with test results. In addition, analytical model representing partially infilled frames was established and analyzed. Test results indicated that strength and energy dissipating capacity were increased for IW-RN(fully infilled frames) compared to the NW(bare frame). The nonlinear static analysis of the three specimens was also conducted using the inelastic plastic hinge frame element and diagonal strut models, and the analytical results successfully simulated the nonlinear behaviour of the specimens in accordance with the test results.